Student perceptions of the current drinking culture in three Australian residential colleges: Drinking motives, consequences and recommendations for harm minimisation strategies. (20th September 2022) - Davidson, Lily; Mefodeva, Valeriya; Walter, Zoe; Hides, Leanne
Abstract: Introduction: Systemic cultural factors related to excessive alcohol consumption have been identified in Australian university residential colleges. In this mixed methods study, we conducted focus groups with student leaders at three Australian residential colleges. We aimed to explore students' perceptions of alcohol use and related consequences in their current college environment and gather feedback from students on the utility of alcohol harm minimisation strategies in this context. Methods: In November 2020, 77 student leaders from three colleges participated in focus groups. Each focus group ran for 1.5–2 hours and included three sections: (i) quantitative survey; (ii) semi‐structured group interview; and (iii) feedback on a potential alcohol harm minimisation workshop. Results: The survey revealed that 81% of participants reported drinking hazardously. Thematic analysis of the interview data indicated many students perceived college as a supportive environment regarding students' alcohol use choices (direct peer pressure to drink was uncommon). However, indirect social influence to drink appeared to maintain a 'culture of intoxication'. Specifically, social norms to attend college events (where drinking is implied) and modelling of excessive drinking were key indirect influences on heavy drinking norms. Students were aware and accepting of many alcohol harm minimisation strategies and interested in improving current strategies. Discussion and Conclusions: Despite the supportive college environment described by students, regarding alcohol use choices, a 'culture of intoxication' driven by indirect social influences was evident. Student leaders' interest in increasing the availability of harm minimisation strategies highlights the potential utility of peer‐led alcohol interventions in colleges.